Modified flow battery electrode capable of simultaneously improving activity and stability and preparation method of modified flow battery electrode
By performing carbon felt pretreatment, nanosheet modification, material load modification, and defect structure formation and activation steps on the flow battery electrode, a modified flow battery electrode with a needle-shaped nanostructured coating was prepared, which solved the problem of insufficient stability of the existing electrode in a strong acid environment, and achieved simultaneous improvement of electrode activity and stability.
Patent Information
- Application Number
- CN202510191743.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The existing flow battery electrodes are difficult to maintain long-term stability in a strong acid environment, resulting in a reduced cycle stability and affecting the service life of energy storage.
Modified flow battery electrodes with a needle-shaped nanostructured coating were prepared by carbon felt pretreatment, nanosheet modification, material load modification, and defect structure formation and activation steps. The method includes high pressure treatment using a mixture of tin tetrachloride, manganese nitrate, melamine and urea, followed by addition of a mixture of nickel nitrate, dopamine hydrochloride, polyamino acid and sodium citrate for further treatment and activation.
The specific surface area, electrochemical activity and stability of the flow battery electrode were significantly improved, the energy efficiency was increased by 13.9%, the stability reached 5 times that of the original electrode, and the cycle stability was significantly improved.
Smart Images

Figure CN119674107A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to liquid flow battery energy storage technology, and in particular to a modified liquid flow battery electrode capable of simultaneously improving activity and stability and a preparation method thereof. Background Art
[0002] Liquid flow battery energy storage, as a new type of energy storage method, has the advantages of inherent safety and green environmental protection, and has become an important form of energy storage. The electrode, as the site of the redox reaction of the liquid flow battery, directly affects the performance of the liquid flow battery. In order to improve the performance of the electrode, physical and chemical treatment, modification, heteroatom and other methods are often used to improve the electrode voltage efficiency, energy efficiency and specific surface area, and reduce the activation polarization, concentration polarization and ohmic polarization of the electrochemical reaction. However, these treatment methods often cannot improve the cycle stability of the electrode because the external substances introduced cannot exist stably for a long time in a strong acid environment, and may even lead to reduced stability, which directly affects the service life of the liquid flow battery after long-term circulation. Therefore, at this stage, there is an urgent need for a modified liquid flow battery electrode that can simultaneously improve activity and stability. Summary of the invention
[0003] In order to overcome the problems in the prior art, the present application provides a modified liquid flow battery electrode and a preparation method thereof that simultaneously improves activity and stability.
[0004] In order to achieve the above object, the present invention provides a method for preparing a modified flow battery electrode with improved activity and stability, which comprises the following steps: (1) The carbon felt is cleaned with ethanol and deionized water, then ultrasonicated and dried to obtain the treated electrode material; (2) adding the treated electrode material to a mixture of tin tetrachloride, manganese nitrate, melamine and urea, subjecting the material to high pressure treatment after magnetic stirring, ultrasonic cleaning and drying to obtain a modified electrode; (3) adding the modified electrode to a mixture of nickel nitrate, melamine and urea and subjecting the mixture to magnetic stirring, high pressure treatment, ultrasonic cleaning and drying to obtain a modified electrode; (4) The modified electrode is immersed in a mixture of nickel nitrate, dopamine hydrochloride, polyamino acid, sodium citrate and ethanol, washed and dried, and then treated at high temperature, acid washed and dried to obtain an activated electrode.
[0005] Preferably, in step (1), the ultrasonic treatment is an ultrasonic oscillation treatment for 20 to 30 min, the cleaning is first cleaning with ethanol and then cleaning with deionized water for 2 to 3 times, and the drying is drying at 60° C. for 10 to 12 h.
[0006] Preferably, in steps (2) and (3), the ultrasonic cleaning is performed by ultrasonic cleaning 2 to 3 times and then drying at 60° C. for 6 to 8 hours.
[0007] Preferably, in steps (2) and (3), the high pressure treatment is carried out in a high pressure reactor at a temperature of 122-128° C. for 2-2.5 h.
[0008] Preferably, in step (4), by weight, the dopamine hydrochloride is 0.30-0.40 parts, the polyamino acid is 0.28-0.30 parts, the nickel nitrate is 0.20-0.35 parts, the sodium citrate is 0.48-0.50 parts, and the volume ratio of ethanol to deionized water is 1:1.
[0009] Preferably, in step (4), by weight, the dopamine hydrochloride is 0.32-0.36 parts, the polyamino acid is 0.28-0.30 parts, the nickel nitrate is 0.24-0.25 parts, the sodium citrate is 0.48-0.50 parts, and the volume ratio of ethanol to deionized water is 1:1.
[0010] Preferably, in step (4), the high temperature treatment is to heat the mixture to 780-820°C at a heating rate of 1-2°C / min under a nitrogen atmosphere and keep the temperature for 1.5-2 h.
[0011] Preferably, in step (4), the acid washing is performed by immersing the sample in a 1-2 mol / L oxalic acid or aminosulfonic acid solution for 2-3 times, and washing with deionized water until the pH of the washing solution is greater than 6.
[0012] Preferably, in step (1), by weight, tin tetrachloride is 0.80-1.0 part, manganese nitrate is 0.45-0.60 part, melamine is 0.25-0.33 part, and urea is 0.11-0.13 part.
[0013] Preferably, in step (1), by weight, tin tetrachloride is 0.86-0.94 parts, manganese nitrate is 0.51-0.55 parts, melamine is 0.25-0.33 parts, and urea is 0.11-0.13 parts.
[0014] The present invention also provides a modified liquid flow battery electrode with improved activity and stability obtained based on the above method: the surface of the activated electrode has a needle-shaped nanostructured film.
[0015] Preferably, the surface area of the activated electrode is greater than 50 m 2 / g, the energy efficiency is improved by 13.9% compared with the original electrode, and the stability is 5 times that of the original electrode.
[0016] Compared with the prior art, the present invention has the following beneficial effects: After electrode pretreatment, nanosheet modification, material loading modification, defect structure formation and activation, the specific surface area of the electrode of the present invention is increased by 2 times compared with the original electrode after physical and chemical pretreatment, reaching 69.4 m 2 / g, which provides abundant reaction sites for the redox reaction of flow batteries, improves the chemical reaction kinetics, and promotes the utilization of electrolyte.
[0017] The introduction of tin (Sn) has optimized the potential, while the introduction of nickel (Ni) has enhanced the adsorption of ions between the electrode and the electrode. The present invention has enhanced the reaction kinetics of the reactants, greatly improved the voltage efficiency, energy efficiency and peak power density, and significantly improved the electrocatalytic activity of the flow battery. After treatment, the energy efficiency has increased by 13.9% compared to the original electrode, and the performance has been greatly improved.
[0018] After defect and optimization steps, the present invention realizes the in-situ polymerization of dopamine hydrochloride on the surface of the modified electrode under the protection of polyamino acid, induces the formation of electrode surface defects and acid-resistant sacrificial protective film, and promotes the transfer of redox reaction centers to the active sites of nanosheets and loads, while creating more active areas. While improving the electrocatalytic activity, the stability of the electrode is also greatly improved. After treatment, the stability can stably maintain the energy efficiency at more than 95% of the first cycle energy efficiency for 5 times that of the original electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The scanning electron microscope image of Example 1 of the present invention is shown in Figure 2, where (a) is the modified electrode structure obtained in step (2). It can be seen that 1-5 um nanosheets are attached, and the electrode surface area is about 41.5 m according to the specific surface area test. 2 / g; (b) is the modified electrode structure obtained in step (3), which shows that the structure is more complex and the size of the nanostructure is reduced, with a surface area of about 50.2 m 2 / g; (c) is the activated electrode structure obtained in step (3), where needle-like nanostructures are coated on the surface, with a surface area of approximately 69.4 m 2 / g.
[0020] Figure 2 : is the peak current of the current-voltage curve of Example 1 of the present invention at different scan rates. 2+ / VO2 + and V 3+ / V 2+ The peak potentials of Example 4 are lower than those of Comparative Example 4, indicating that the electrode performance of Example 1 is improved.
[0021] Figure 3 The current density of Example 1 of the present invention is 100 mA / cm2 The energy efficiency changes after multiple cycles, and its cycle stability can exceed 1600 times, while the cycle stability of comparative example 4 is only maintained at 306 times.
[0022] Figure 4 It is a technical roadmap of the method described in the present invention. DETAILED DESCRIPTION
[0023] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present application will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. In addition, in the following description, the description of known technical information is omitted to avoid confusion and confusion.
[0024] A modified flow battery electrode with improved activity and stability comprises the following steps: (1) Carbon felt pretreatment. Cut the commercial carbon felt into small square pieces with a side length of 8 to 10 cm. Wash it with anhydrous ethanol 2 to 3 times, treat it under ultrasonic vibration for 20 to 30 min, and then wash it with deionized water 2 to 3 times. Dry it in a 60°C oven for 10 to 12 h before use. (2) Nanosheet modification. Under magnetic stirring, 0.86-0.94 g of tin tetrachloride, 0.71-0.77 g of manganese nitrate tetrahydrate, 0.25-0.33 g of melamine and 0.11-0.13 g of urea were mixed in 23-27 mL of deionized water and treated under magnetic stirring for 20-30 min. The two pieces of carbon felt obtained in step 1 and the above solution were placed in a polytetrafluoroethylene liner and reacted in a high-pressure reactor at 122-128 °C for 2-2.5 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed 2-3 times and dried in a 60 °C oven for 6-8 h to obtain electrode-loaded SnMnO4 nanosheets; (3) Modification of carbon felt material loading. Under magnetic stirring, mix 0.78-0.80 g nickel nitrate hexahydrate, 0.25-0.33 g melamine and 0.11-0.13 g urea in 23-27 mL deionized water and treat under magnetic stirring for 20-30 min. Place the two electrode-loaded SnMnO4 nanosheets obtained in step 2 and the above-obtained solution into a polytetrafluoroethylene liner and react in a high-pressure reactor at 122-128 °C for 2-2.5 h. After the reaction is completed and cooled to room temperature, ultrasonically clean it 2-3 times and place it in a 60 °C oven to dry for 6-8 h. Obtain electrode-loaded SnMnO4 / Ni(OH)2 composite nanosheets; (4) Defect formation and activation. Under magnetic stirring, add 0.32-0.36 g dopamine hydrochloride, 0.28-0.30 g polyamino acid, 0.39-0.40 g nickel nitrate hexahydrate and 0.55-0.57 g sodium citrate dihydrate into 35-45 mL ethanol and deionized water (volume ratio 1:1). Immerse the two electrodes obtained in step 3 in the above solution and stir magnetically for 2-3 h, then dry at 60°C for 10-12 h. Treat the obtained electrode at 780-820°C for 1.5-2 h at a heating rate of 1-2°C / min under a nitrogen atmosphere. After natural cooling, immerse the sample in 1-2 mol / L oxalic acid or aminosulfonic acid solution for 2-3 times, and wash with deionized water until the pH of the washing solution is greater than 6. The electrode product is dried at 60°C for 10-12 h. The obtained activated electrodes are assembled into a stack and various performance tests are performed.
[0025] Example 1 (1) Cut the commercial carbon felt into small square pieces with a side length of 9 cm. Wash it three times with anhydrous ethanol, treat it under ultrasonic vibration for 25 min, and then wash it three times with deionized water. Dry it in a 60℃ oven for 11 h before use. Its surface area is about 23.2 m 2 / g, (2) Under magnetic stirring, 0.90 g of tin tetrachloride, 0.74 g of manganese nitrate tetrahydrate, 0.29 g of melamine and 0.12 g of urea were mixed in 25 mL of deionized water and treated under magnetic stirring for 25 min. The two pieces of carbon felt obtained in step 1 and the above solution were placed in a polytetrafluoroethylene liner and reacted in a high-pressure reactor at 125°C for 2.5 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed three times and dried in an oven at 60°C for 7 h to obtain electrode-loaded SnMnO4 nanosheets. This structure is a nanosheet structure grown on the electrode surface, such as Figure 1 Part (a) in the figure greatly increases the specific surface area of the electrode. The area mass loading of this structure is 0.53 mg / cm 2 Due to potential adjustment and other reasons, the introduction of Sn improves the energy efficiency by 6.7% compared with the original electrode and maintains higher cycle stability. Its surface area is about 41.5 m 2 / g; (3) Under magnetic stirring, 0.79 g nickel nitrate hexahydrate, 0.29 g melamine and 0.12 g urea were mixed in 25 mL deionized water and treated under magnetic stirring for 25 min. The two electrode-loaded SnMnO4 nanosheets obtained in step 2 and the above solution were placed in a polytetrafluoroethylene liner and reacted in a high-pressure reactor at 125°C for 2.5 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed 3 times and dried in an oven at 60°C for 7 h. Electrode-loaded SnMnO4 / Ni(OH)2 composite nanosheets were obtained. The area mass loading of the structure was 0.66 mg / cm 2 , the structure is as follows Figure 1 Part (b) of the figure. The introduction of Ni strengthens the adsorption of counter ions and improves the reaction kinetics, further improving the energy efficiency by 2.1% compared to the electrode in step 2. Its surface area is about 50.2 m 2 / g; (4) Under magnetic stirring, add 0.34 g dopamine hydrochloride, 0.29 g polyamino acid, 0.40 g nickel nitrate hexahydrate and 0.56 g sodium citrate dihydrate into 40 mL ethanol and deionized water (volume ratio 1:1). Immerse the two electrodes obtained in step 3 in the above solution and stir magnetically for 2.5 h, then dry at 60°C for 11 h. Heat the obtained electrode at a heating rate of 1.5°C / min under a nitrogen atmosphere to 800°C and keep it for 1.5 h. After natural cooling, the sample is immersed in a 1.5 mol / L oxalic acid or aminosulfonic acid solution and washed three times, and then washed with deionized water until the pH of the washing solution is greater than 6. The electrode product is dried at 60°C for 11 h. The obtained electrodes are assembled into a stack and various performance tests are performed. By increasing the specific surface area, more reaction sites are provided for redox reactions, such as Figure 1 In part (c), the energy efficiency and peak power density are greatly improved, which significantly improves the electrocatalytic activity and stability of the all-vanadium liquid flow battery. The surface area is about 69.4 m 2 / g, which is three times that of the original electrode. The energy efficiency is improved by 13.9% compared with the original electrode, and the stability is 5 times that of the original electrode.
[0026] Example 2 (1) Cut the commercial carbon felt into small square pieces with a side length of 8 cm. Wash it with anhydrous ethanol three times, treat it under ultrasonic vibration for 20 min, and then wash it with deionized water three times. Dry it in an oven at 60℃ for 12 h before use. (2) Under magnetic stirring, 0.86 g of tin tetrachloride, 0.77 g of manganese nitrate tetrahydrate, 0.25 g of melamine and 0.13 g of urea were mixed in 27 mL of deionized water and treated under magnetic stirring for 20 min. The two pieces of carbon felt obtained in step 1 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 128°C for 2 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed 3 times and dried in an oven at 60°C for 6 h to obtain electrode-loaded SnMnO4 nanosheets. The area mass loading of the structure was 0.54 mg / cm 2 ; (3) Under magnetic stirring, 0.78 g nickel nitrate hexahydrate, 0.33 g melamine and 0.11 g urea were mixed in 27 mL deionized water and treated under magnetic stirring for 20 min. The two electrode-loaded SnMnO4 nanosheets obtained in step 2 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 122 °C for 2.5 h. After cooling to room temperature, ultrasonic cleaning was performed twice and the nanosheets were dried in an oven at 60 °C for 8 h. The electrode-loaded SnMnO4 / Ni(OH)2 composite nanosheets were obtained with an area mass loading of 0.64 mg / cm 2 ; (4) Under magnetic stirring, 0.36 g dopamine hydrochloride, 0.28 g polyamino acid, 0.40 g nickel nitrate hexahydrate and 0.55 g sodium citrate dihydrate were added to 45 mL ethanol and deionized water (volume ratio 1:1). The two electrodes obtained in step 3 were immersed in the above solution and magnetically stirred for 2 h, and then dried at 60°C for 12 h. The obtained electrode was treated at 820°C for 1.5 h at a heating rate of 1°C / min under a nitrogen atmosphere. After natural cooling, the sample was immersed in a 2 mol / L oxalic acid or aminosulfonic acid solution and washed twice, and then washed with deionized water until the pH of the washing solution was greater than 6. The electrode product was dried at 60°C for 12 h. The obtained electrodes were assembled into a stack and various performance tests were performed.
[0027] Example 3 (1) Cut the commercial carbon felt into small square pieces with a side length of 10 cm. Wash it twice with anhydrous ethanol, treat it under ultrasonic vibration for 30 min, and then wash it twice with deionized water. Dry it in an oven at 60℃ for 10 h before use. (2) Under magnetic stirring, 0.94 g of tin tetrachloride, 0.71 g of manganese nitrate tetrahydrate, 0.33 g of melamine and 0.11 g of urea were mixed in 23 mL of deionized water and treated under magnetic stirring for 30 min. The two pieces of carbon felt obtained in step 1 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 122°C for 2.5 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed twice and dried in an oven at 60°C for 8 h to obtain electrode-loaded SnMnO4 nanosheets. The area mass loading of the structure was 0.52 mg / cm 2 ; (3) Under magnetic stirring, 0.80 g nickel nitrate hexahydrate, 0.25 g melamine and 0.13 g urea were mixed in 23 mL deionized water and treated under magnetic stirring for 30 min. The two electrode-loaded SnMnO4 nanosheets obtained in step 2 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 128 °C for 2 h. After cooling to room temperature, ultrasonic cleaning was performed three times and dried in an oven at 60 °C for 6 h. Electrode-loaded SnMnO4 / Ni(OH)2 composite nanosheets were obtained. The area mass loading was 0.68 mg / cm 2 ; (4) Under magnetic stirring, 0.32 g dopamine hydrochloride, 0.30 g polyamino acid, 0.39 g nickel nitrate hexahydrate and 0.57 g sodium citrate dihydrate were added to 35 mL ethanol and deionized water (volume ratio 1:1). The two electrodes obtained in step 3 were immersed in the above solution and magnetically stirred for 3 h, and then dried at 60°C for 10 h. The obtained electrode was treated at 780°C for 2 h at a heating rate of 2°C / min under a nitrogen atmosphere. After natural cooling, the sample was immersed in 1 mol / L oxalic acid or aminosulfonic acid solution for washing 3 times, and then washed with deionized water until the pH of the washing solution was greater than 6. The electrode product was dried at 60°C for 10 h. The obtained electrodes were assembled into a stack and various performance tests were performed.
[0028] Example 4 (1) Cut the commercial carbon felt into small square pieces with a side length of 8 cm. Wash it twice with anhydrous ethanol, treat it under ultrasonic vibration for 20 min, and then wash it twice with deionized water. Dry it in an oven at 60℃ for 10 h before use. (2) Under magnetic stirring, 0.86 g of tin tetrachloride, 0.71 g of manganese nitrate tetrahydrate, 0.25 g of melamine and 0.11 g of urea were mixed in 23 mL of deionized water and treated under magnetic stirring for 20 min. The two pieces of carbon felt obtained in step 1 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 122°C for 2 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed twice and dried in an oven at 60°C for 6 h to obtain electrode-loaded SnMnO4 nanosheets. The area mass loading of the structure was 0.52 mg / cm 2 ; (3) Under magnetic stirring, 0.78 g nickel nitrate hexahydrate, 0.25 g melamine and 0.11 g urea were mixed in 23 mL deionized water and treated under magnetic stirring for 20 min. The two electrode-loaded SnMnO4 nanosheets obtained in step 2 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 122 °C for 2 h. After cooling to room temperature, ultrasonic cleaning was performed twice and dried in an oven at 60 °C for 6 h. Electrode-loaded SnMnO4 / Ni(OH)2 composite nanosheets were obtained. The mass loading was 0.64 mg / cm 2 ; (4) Under magnetic stirring, 0.32 g dopamine hydrochloride, 0.28 g polyamino acid, 0.39 g nickel nitrate hexahydrate and 0.55 g sodium citrate dihydrate were added to 35 mL ethanol and deionized water (volume ratio 1:1). The two electrodes obtained in step 3 were immersed in the above solution and magnetically stirred for 2 h, and then dried at 60°C for 10 h. The obtained electrode was treated at 780°C for 1.5 h at a heating rate of 1°C / min under a nitrogen atmosphere. After natural cooling, the sample was immersed in 1 mol / L oxalic acid or aminosulfonic acid solution for washing twice, and then washed with deionized water until the pH of the washing solution was greater than 6. The electrode product was dried at 60°C for 10 h. The obtained electrodes were assembled into a stack and various performance tests were performed.
[0029] Example 5 (1) Cut the commercial carbon felt into small square pieces with a side length of 10 cm. Wash it with anhydrous ethanol three times, treat it under ultrasonic vibration for 30 min, and then wash it with deionized water three times. Dry it in an oven at 60℃ for 12 h before use. (2) Under magnetic stirring, 0.94 g of tin tetrachloride, 0.77 g of manganese nitrate tetrahydrate, 0.33 g of melamine and 0.13 g of urea were mixed in 27 mL of deionized water and treated under magnetic stirring for 30 min. The two pieces of carbon felt obtained in step 1 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 128°C for 2.5 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed three times and dried in an oven at 60°C for 8 h to obtain electrode-loaded SnMnO4 nanosheets. The area mass loading of the structure was 0.54 mg / cm 2 ; (3) Under magnetic stirring, 0.80 g nickel nitrate hexahydrate, 0.33 g melamine and 0.13 g urea were mixed in 27 mL deionized water and treated under magnetic stirring for 30 min. The two electrode-loaded SnMnO4 nanosheets obtained in step 2 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 128 °C for 2.5 h. After cooling to room temperature, ultrasonic cleaning was performed three times and dried in an oven at 60 °C for 8 h. Electrode-loaded SnMnO4 / Ni(OH)2 composite nanosheets were obtained. The area mass loading was 0.68 mg / cm 2 ; (4) Under magnetic stirring, 0.36 g dopamine hydrochloride, 0.30 g polyamino acid, 0.40 g nickel nitrate hexahydrate and 0.57 g sodium citrate dihydrate were added to 45 mL ethanol and deionized water (volume ratio 1:1). The electrode obtained in step 3 was immersed in the above solution. The two electrodes obtained in step 3 were immersed in the above solution and magnetically stirred for 3 h, and then dried at 60°C for 12 h. The obtained electrode was treated at 820°C for 2 h at a heating rate of 2°C / min under a nitrogen atmosphere. After natural cooling, the sample was immersed in a 2 mol / L oxalic acid or aminosulfonic acid solution for washing 3 times, and then washed with deionized water until the pH of the washing solution was greater than 6. The electrode product was dried at 60°C for 12 h. The obtained electrodes were assembled into a stack and various performance tests were performed.
[0030] Comparative Example 1 (1) Cut the commercial carbon felt into small square pieces with a side length of 9 cm. Wash it with anhydrous ethanol three times, treat it under ultrasonic vibration for 25 min, and then wash it with deionized water three times. Dry it in an oven at 60℃ for 11 h before use. (2) Under magnetic stirring, 0.90 g of tin tetrachloride, 0.74 g of manganese nitrate tetrahydrate, 0.29 g of melamine and 0.12 g of urea were mixed in 25 mL of deionized water and treated under magnetic stirring for 25 min. The two pieces of carbon felt obtained in step 1 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 125°C for 2.5 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed 3 times and dried in an oven at 60°C for 7 h to obtain electrode-loaded SnMnO4 nanosheets; (3) Under magnetic stirring, 0.79 g nickel nitrate hexahydrate, 0.29 g melamine and 0.12 g urea were mixed in 25 mL deionized water and treated under magnetic stirring for 25 min. The two electrode-loaded SnMnO4 nanosheets obtained in step 2 and the above solution were placed in a polytetrafluoroethylene liner and reacted in an autoclave at 125°C for 2.5 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed three times and dried in an oven at 60°C for 7 h. The obtained electrodes were assembled into a stack and various performance tests were performed.
[0031] Comparative Example 2 (1) Cut the commercial carbon felt into small square pieces with a side length of 9 cm. Wash it with anhydrous ethanol three times, treat it under ultrasonic vibration for 25 min, and then wash it with deionized water three times. Dry it in an oven at 60℃ for 11 h before use. (2) Under magnetic stirring, 0.90 g of tin tetrachloride, 0.74 g of manganese nitrate tetrahydrate, 0.29 g of melamine and 0.12 g of urea were mixed in 25 mL of deionized water and treated under magnetic stirring for 25 min. The two pieces of carbon felt obtained in step 1 and the above solution were placed in a polytetrafluoroethylene liner and reacted in a high-pressure reactor at 125°C for 2.5 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed 3 times and dried in a 60°C oven for 7 h. The obtained electrodes were assembled into a stack and various performance tests were performed.
[0032] Comparative Example 3 (1) Cut the commercial carbon felt into small square pieces with a side length of 9 cm. Wash it with anhydrous ethanol three times, treat it under ultrasonic vibration for 25 min, and then wash it with deionized water three times. Dry it in an oven at 60℃ for 11 h before use. (2) Under magnetic stirring, 0.79 g nickel nitrate hexahydrate, 0.29 g melamine and 0.12 g urea were mixed in 25 mL deionized water and treated under magnetic stirring for 25 min. The two electrodes obtained in step 1 and the above solution were placed in a polytetrafluoroethylene liner and reacted in a high-pressure reactor at 125°C for 2.5 h. After the reaction was completed and cooled to room temperature, ultrasonic cleaning was performed three times and dried in a 60°C oven for 7 h. The obtained electrodes were assembled into a stack and various performance tests were performed.
[0033] Comparative Example 4 (1) Commercial carbon felt was cut into small square pieces with a side length of 9 cm. It was washed with anhydrous ethanol three times, treated under ultrasonic vibration for 25 min, and then washed with deionized water three times. It was placed in a 60°C oven and dried for 11 h. The obtained electrodes were assembled into a battery stack and various performance tests were performed.
[0034] Table 1. Performance comparison of examples and comparative examples , As can be seen from the above table, the specific surface area, energy efficiency, voltage efficiency and cycle stability of the electrodes of several embodiments are not much different, but are greatly improved compared with several comparative examples, indicating that after electrode pretreatment, nanosheet modification, material loading modification, defect structure formation and activation, the present invention effectively improves the electrochemical activity and stability of the electrode.
[0035] The performance of Comparative Example 3 is slightly improved compared with Comparative Example 4, indicating that the introduction of Ni enhances the reaction kinetics of the reactants by strengthening the adsorption of electrodes and counterions, greatly improving the voltage efficiency, energy efficiency and peak power density, and significantly improving the electrocatalytic activity of the flow battery. The performance of Comparative Example 2 is improved compared with Comparative Example 4, indicating that the introduction of Sn has adjusted and optimized the potential, reduced the reaction overpotential, reduced efficiency loss, and improved stability. The performance of Comparative Example 2 is improved compared with Comparative Example 3, indicating that Sn has a higher performance-promoting effect than Ni in this invention. The performance of Comparative Example 1 is improved compared with Comparative Examples 2 and 3, indicating that the synergistic effect of Sn and Ni is better than the gain brought by the addition of a single metal.
[0036] In addition, the performance of the embodiment is improved compared with that of comparative example 1, indicating that after the defect and optimization steps, the in-situ polymerization of dopamine hydrochloride on the surface of the modified electrode is achieved under the protection of the polyamino acid, which induces the formation of defects on the electrode surface and the acid-resistant sacrificial protective film, and promotes the transfer of the redox reaction center to the active sites of the nanosheet and the load, while creating more active areas. While improving the electrocatalytic activity, the stability of the electrode is also greatly improved.
[0037] By adjusting and optimizing the raw material ratio and experimental parameters of the embodiments, the specific surface area, energy efficiency, voltage efficiency and cycle stability can be slightly improved. This is reflected in the partial differences in the performance of Examples 1 to 5 in the table, which is mainly related to the introduction ratio of Sn and Ni. The electrochemical activity of the flow battery can be improved by adjusting and optimizing the potential and strengthening the adsorption of electrodes and counterions. The ratio of dopamine hydrochloride to polyamino acids also affects the degree of in situ polymerization on the surface of the modified electrode and the number of active sites of the redox reaction center transferred to the nanosheets and loads, which has a certain degree of influence on the cycle stability. The voltage efficiency of several embodiments is 87.9~89.2%, the energy efficiency is 85.8~87.1%, and the specific surface area is 66.7~69.4 m 2 / g, and the cycle stability is 1412~1649 times.
[0038] The present invention provides a modified liquid flow battery electrode that improves both activity and stability. After electrode pretreatment, nanosheet modification, material loading modification, defect structure formation and activation, the activity and stability of the electrode are improved at the same time. The specific surface area of the electrode of the present invention is increased from the original electrode after physical and chemical pretreatment, which improves the chemical reaction kinetics and promotes the utilization of the electrolyte. After the introduction of Sn, the potential is adjusted and optimized, and the introduction of Ni strengthens the adsorption of the electrode and the electrode ions. The present invention strengthens the reaction kinetics of the reactants, greatly improves the voltage efficiency, energy efficiency and peak power density, and significantly improves the electrocatalytic activity of the liquid flow battery. After the defect and optimization steps, the redox reaction center is promoted to transfer to the active sites of the nanosheet and the load, and more active area is created. While improving the electrocatalytic activity, the stability of the electrode is also greatly improved.
[0039] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a modified flow battery electrode with improved activity and stability, characterized in that: The following steps are included: (1) The carbon felt is cleaned with ethanol and deionized water, then ultrasonicated and dried to obtain the treated electrode material; (2) adding the treated electrode material to a mixture of tin tetrachloride, manganese nitrate, melamine and urea, subjecting the material to high pressure treatment after magnetic stirring, ultrasonic cleaning and drying to obtain a modified electrode; (3) adding the modified electrode to a mixture of nickel nitrate, melamine and urea and subjecting the mixture to magnetic stirring, high pressure treatment, ultrasonic cleaning and drying to obtain a modified electrode; (4) The modified electrode is immersed in a mixture of nickel nitrate, dopamine hydrochloride, polyamino acid, sodium citrate and ethanol, washed and dried, and then treated at high temperature, acid washed and dried to obtain an activated electrode.
2. The method for preparing a modified flow battery electrode with improved activity and stability according to claim 1, characterized in that: In step (1), the ultrasonic treatment is an ultrasonic oscillation treatment for 20 to 30 min, the cleaning is firstly cleaning with ethanol and then cleaning with deionized water for 2 to 3 times, and the drying is drying at 60° C. for 10 to 12 h.
3. The method for preparing a modified liquid flow battery electrode with improved activity and stability according to claim 1, characterized in that: In steps (2) and (3), the ultrasonic cleaning is performed by ultrasonic cleaning 2 to 3 times and then drying at 60° C. for 6 to 8 hours.
4. The method for preparing a modified liquid flow battery electrode with improved activity and stability according to claim 1, characterized in that: In steps (2) and (3), the high pressure treatment is carried out in a high pressure reactor at a temperature of 122-128° C. for 2-2.5 h.
5. The method for preparing a modified liquid flow battery electrode with improved activity and stability according to claim 1, characterized in that: In step (4), by weight, the dopamine hydrochloride is 0.30-0.40 parts, the polyamino acid is 0.28-0.30 parts, the nickel nitrate is 0.20-0.35 parts, the sodium citrate is 0.48-0.50 parts, and the volume ratio of ethanol to deionized water is 1:
1.
6. The method for preparing a modified liquid flow battery electrode with improved activity and stability according to claim 1, characterized in that: In step (4), the high temperature treatment is to heat the mixture to 780-820°C at a heating rate of 1-2°C / min under a nitrogen atmosphere and keep the temperature for 1.5-2 h.
7. The method for preparing a modified liquid flow battery electrode with improved activity and stability according to claim 1, characterized in that: In step (4), the acid washing is performed by immersing the sample in a 1-2 mol / L oxalic acid or aminosulfonic acid solution for 2-3 times, and then washing with deionized water until the pH of the washing solution is greater than 6.
8. The method for preparing a modified liquid flow battery electrode with improved activity and stability according to claim 1, characterized in that: In step (1), by weight, tin tetrachloride is 0.80-1.0 part, manganese nitrate is 0.45-0.60 part, melamine is 0.25-0.33 part, and urea is 0.11-0.13 part.
9. A modified liquid flow battery electrode with improved activity and stability obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The surface of the activated electrode is coated with a needle-shaped nanostructure film.
10. The modified liquid flow battery electrode with improved activity and stability according to claim 9, characterized in that: The surface area of the activated electrode is greater than 50 m 2 / g, the energy efficiency is improved by 13.9% compared with the original electrode, and the stability is 5 times that of the original electrode.
Citation Information
Patent Citations
Fuel cell catalyst taking carbon-coated conductive ceramics as supporter and preparation method thereof
CN102082279A
Nano particle / carbon fiber cloth composite electrode material and preparation method thereof
CN109216663A
Preparation method of stannic oxide / manganese dioxide and carbon cloth flexible composite electrode
CN112164596A
Conductive carbon substrate loaded graphene aerogel composite electrode and preparation method thereof
CN112467111A
Tin-manganese stannate-nitrogen carbon composite material with hollow cubic structure as well as preparation method and application thereof
CN113363441A
Cited By
Flow battery electrode for improving cycling stability and electrochemical performance and preparation method
CN121748411A